The Role of Ret Genomic Variants in Infantile Hypertrophic Pyloric Stenosis - Serra, A.; Schuchardt, K.; Genuneit, J.; Leriche, C.; Görgens, H. S.; Schackert, H.-K; Fitze, G. (European Journal of Pediatric Surgery, 2011)
Infantile hypertrophic pyloric stenosis (IHPS) is a common childhood pathology affecting approximately 1–5 children pro 1 000 newborns, with a genetic background as suggested by the familial occurrence. RET is a candidate gene for IHPS due to its role in the development of the intrinsic innervation and ganglia of the smooth musculature and the association of RET variants with another motility disorder (Hirschsprung’s disease). Accordingly, we investigated RET-IHPS associations through sequencing of the complete RET coding region in 32 IHPS patients. Genotype frequencies were compared between patients and 48 controls using the Cochran-Armitage trend test or Fischer’s test for exact p-values. We found 19 RET variants in IHPS, including polymorphisms in the promoter region (c.-200 G>A and c.-196C>A). There was no statistically significant difference between the frequencies of the variants in both groups. There was no deviation from the Hardy-Weinberg equilibrium, yet a significant correlation (linkage disequilibrium) for variants in the promoter region, in exons 11, 13, 14 and 19 and in the 3’ UTR. We conclude that RET variants are present in IHPS patients yet show no significant statistical association with the IHPS phenotype, suggesting at best an adjuvant role for RET in IHPS.
Keywords: infantile hypertrophic pyloric stenosis; RET proto-oncogene; mutations; polymorphisms